P29 Exercise intolerance in chronic thromboembolic disease: evaluation, underlying mechanisms and clinical implications. (15th November 2016) - Swietlik, EM; Taboada, D; Ruggiero, A; Bales, E; Harlow, L; Fletcher, A; Cannon, JE; Sheares, K; Jenkins, DP; Pepke-Zaba, J; Toshner, T
Abstract : Introduction: Patients with chronic thromboembolic disease (CTED) without pulmonary hypertension commonly present with dyspnoea and fatigue. These symptoms limit physical function and impair quality of life. As resting haemodynamics in these patients are normal or near normal, stress testing may be a useful investigation to clarify mechanisms of functional impairment. Methods: We prospectively evaluated baseline characteristics of patients with CTED in a single referral centre between January 2015 and June 2016. Newly referred patients with suspected CTED underwent a standard assessment as delineated in international guidelines 1 with a minimum of 2 imaging modalities, resting and exercise right heart catheterisation (RHC) and additionally incremental cardiopulmonary exercise testing (CPET). All patients were assessed in a pulmonary endarterectomy MDT. Results: Of 21 patients with confirmed CTED, 16 have completed the full assessment protocol (median age 53, 47–62). 14 (87%) were in functional class II/III. All patients had normal right ventricular function on echocardiography. Airway obstruction was present in 7 patients (44.5%). In majority of patients peak VO2 and oxygen pulse were decreased and VE/VCO2 at anaerobic threshold (AT) was increased (Table 1 ). CPET revealed 3 types of exercise limitation: combined cardiovascular and ventilatory limitation (n = 12), ventilatory limitation (n = 2) and limitation due to other reasons (n = 2). Peak oxygen consumption correlated with the symptoms domain of CAMPHOR (pulmonary hypertension specific quality of life measure) (p = 0.0242, R 0.56), cardiac output increase on exercise (p = 0.03, R 0.569) and VE/VCO2 at anaerobic threshold (p = 0.012, R 0.608). Resting mPAP and PVR did not correlate with peak VO2 or symptoms. Conclusions: We confirm the limited utility of resting measurements, including RHC in CTED for understanding exercise and functional limitation. CPET identified alternative causes for breathlessness and clarifies that patients with CTED are limited on exertion because of inability to increase cardiac output and hyperventilation. Reference: Galie N, et al . ESC/ERS Guidelines for the diagnosis and treatment of pulmonary hypertension. EHJ 2015;58 (1):e129–e152.